Corporate Social and Environmental Reporting in OHADA Context: Evidence from Companies Listed on the Douala Stock Exchange - Nganthou, Alexis; Boukar, Hamadou; Djeugou, Gaelle (Research Journal of Finance and Accounting, 2019)
This research questions the capacity of the OHADA accounting system to report on the societal commitment of companies. To carry out such a study, we are interested in the companies of the Douala Stock Exchange, which permanently publish green operations. The analysis was done at two levels: the first level of analysis highlighted the categories of green operations reported by the companies of our sample. The second level of analysis consisted in analysing the financial statements produced by these companies, in order to see in which accounts green transactions are recorded. The analysis reveals that, apart from some additional clarifications to be made in the appendices, the financial statements produced according to OHADA do not specifically highlight green information.
OpenAlex: https://openalex.org/W2998516176
Keywords: Carry (investment); Green operations; Publication; Sample (material); Societal commitment; Stock (firearms)

Shareholder activism, corporate social responsibility and financial performance - Yang, Yi (Victoria University of Wellington, 2019)
The thesis examines the influence of shareholder activism on corporate social responsibility (CSR) disclosure of targeted firms and its spillover effects on CSR disclosure, corporate social performance (CSP) and financial performance (FP) respectively in peer firms. The research is motivated by filling the research gaps in prior literature and providing insights to shareholders, the management and regulatory bodies in practice. The thesis consists of three parts. Firstly, this thesis reviews the literature surrounding shareholder activism by conducting narrative reviews of 92 working papers and publications and meta-analysis on 55 working papers and publications, published during 2000-2017 period. Theories from prior literature, namely agency theory, stakeholder theory and stakeholder salience theory are analysed through narrative review analysis at the beginning of the chapter. Then, the analysis of narrative review also documents mixed findings of the associations among shareholder activism and FP and CG and CSP, including spillover effects. That is, the associations could be positive, negative and not significant in prior literature. The results of meta-analysis indicate that shareholder activism improves FP and CSP respectively. In addition, the thesis also examines the major types of shareholder activists and main forms of shareholder activism. Overall, through the analysis, the thesis identifies the research gaps of prior literature, thereby pointing out future research directions. Secondly, by employing shareholder proposals from Standard & Poor's 1,500 (S&P 1,500, hereafter) companies in the United States as a proxy of shareholder activism during 2006-2014 period with 13,572 separate observations, this thesis examines whether the whole sample of shareholder activism, institutional shareholder activism and coordinated shareholder activism could influence CSR disclosure level respectively. Simultaneously, this thesis also investigates whether shareholder activism affects CSR disclosure level given the other corporate governance mechanisms, namely board size, the presence of female directors, outside directors and CEO incentives. The results typically demonstrate that: (1) while shareholder activism negatively relates to CSR disclosure level, larger board size or the presence of female directors combined with shareholder activism directly relates to maintaining better CSR transparency; (2) coordinated shareholder activism could decrease social disclosure level. The findings also indicate that CSR disclosure provides an approach to strategically manage risks. Thirdly, the thesis explores spillover effects from different types of shareholder activism on CSR disclosure level, CSP and financial performance by using data gathered from S&P 1,500 companies during 2007-2014 period. The findings show that shareholder activism increases social disclosure level and environmental disclosure level in peer firms. It also shows that there is a weak positive association between shareholder activism and CSP. It therefore demonstrates the weak influences of shareholder activism in changing firms’ CSP. It also illustrates that institutional shareholder activism has an advantage over coordinated shareholder activism in terms of increasing corporate transparency. In this manner, it indicates that the collective action problem among coordinated shareholders could also attenuate the impact of shareholder activism in peer firms. The thesis contributes to the literature on shareholder activism practically and theoretically. The findings provide useful insights to shareholders, management teams and regulatory bodies for their policy-making. Beyond the practical contribution, the thesis also provides empirical evidence to stakeholder salience theory and analyses the collective action problem.
Keywords: CSR disclosure; Corporate Social Responsibility; Corporate governance; Corporate social performance; Financial performance; Shareholder activism